Lactate Albumin Ratio Is Associated With Mortality in Patients With Moderate to Severe Traumatic Brain Injury - Wang, Ruoran; He, Min; Qu, Fengyi; Zhang, Jing; Xu, Jianguo (Frontiers in Neurology, 2022)
Background Traumatic brain injury (TBI) is a serious public health issue all over the world. This study was designed to evaluate the prognostic value of lactate to albumin ratio (LAR) on patients with moderate to severe traumatic brain injury. Methods Clinical data of 273 moderate to severe TBI patients hospitalized in West China Hospital between May 2015 and January 2018 were collected. Multivariate logistic regression analyses were used to explore risk factors and construct prognostic model of in-hospital mortality in this cohort. Receiver operating characteristic (ROC) curve was drawn to evaluate discriminative ability of this model. Results Non-survivors had higher LAR than survivors (1.09 vs 0.53, p<0.001). Results of multivariate logistic regression analysis showed that GCS (OR=0.743, p=0.001), blood glucose (OR=1.132, p=0.005), LAR (OR=1.698, p=0.022), subdural hematoma (OR=2.889, p=0.006), intraparenchymal hemorrhage (OR=2.395, p=0.014) and diffuse axonal injury (OR=2.183, p=0.041) were independent risk factors of in-hospital mortality in included patients. These six factors were utilized to construct the prognostic model. The area under the ROC curve (AUC) value of single lactate, albumin and LAR were 0.733 (95%Cl; 0.673-0.794), 0.740 (95%Cl; 0.683-0.797) and 0.780 (95%Cl; 0.725-0.835), respectively. The AUC value of the prognostic model was 0.857 (95%Cl; 0.812-0.901), which was higher than that of LAR (Z=2.1250, p<0.05). Conclusions LAR is a readily available prognostic marker of moderate to severe TBI patients. Prognostic model incorporating LAR is beneficial for clinicians to evaluate possible progression and make treatment decisions in TBI patients.